Many roads to Rome: The emergence of pathways from patterns of change through exploratory modelling of sustainability transitions. (November 2016) - de Haan, Fjalar J.; Rogers, Briony C.; Brown, Rebekah R.; Deletic, Ana
Abstract: This article presents an exploratory modelling approach that illustrates how overall transition pathways can emerge from a limited number of underlying change patterns. Pathways describe the temporal development of transitions, they are trajectories of change that carry societal systems such as health care, energy supply or water management into qualitatively different states. Under any given input scenario, a very large number of different pathways may result due to uncertainties such as those related to human agency. Though the pathways all differ in detail, clusters of pathways share enough qualitative similarities to allow identification of a small number of ideal types: many roads to Rome. The input scenario influences how often the various types of futures emerge, not what types emerge. The article explores this using a series of hypothetical cases and compares the results with ideal-typical pathways from the literature. A historical case is simulated for illustration. Highlights: An exploratory modelling approach for sustainability transitions is presented. Sustainability transition pathways from the literature are reproduced bottom up. Any single scenario may give rise to several different types of future pathways. Different scenarios lead to similar kinds of future pathways: many roads to Rome. Scenarios influence how often types of futures emerge, not what types emerge.